Establishing a new efficiency descriptor for methanol oxidation reaction and its validation with commercially available Pt-based catalysts - Deshpande, Pooja S.; Radhakrishnan, Thulasi; Prasad, Bhagavatula L. V. (Fuel Cells, 2024)
Direct methanol fuel cells (DMFCs) have received a lot of attention in recent years as promising technology for generating clean and efficient energy. In DMFC, the anode catalyst is a vital component because it is involved in the oxidation of methanol, which produces electrons that can be used as an energy source. Cyclic voltammetry (CV) is commonly used to test the characteristics of the electrode materials before they are employed in the actual fuel cell. Interestingly in the case of DMFCs CV also is a useful technique to obtain vital information about the performance and expected efficiency of the electrodes. In general, the CV of methanol electrooxidation for Pt-based catalysts has two peaks, If in the forward scan (anodic scan) and Ib in the backward scan (cathodic scan). The ratio of these two peaks (If/Ib) is the most commonly used criterion for investigating CO poisoning in catalysts. However, there is a great deal of ambiguity surrounding this criterion, owing to the genesis of Ib. Addressing this we present here a new criterion to evaluate the efficiency of the catalyst using the same CV technique. We validate this newly proposed criterion with commercial Pt/C (comm. Pt/C) and other commercially available alloy catalysts.
Keywords: catalyst poisoning; CO tolerance; direct methanol fuel cells; electrocatalysis; Methanol oxidation reaction